2014
DOI: 10.3389/fpls.2014.00427
|View full text |Cite
|
Sign up to set email alerts
|

TCPs, WUSs, and WINDs: families of transcription factors that regulate shoot meristem formation, stem cell maintenance, and somatic cell differentiation

Abstract: In contrast to somatic mammalian cells, which cannot alter their fate, plant cells can dedifferentiate to form totipotent callus cells and regenerate a whole plant, following treatment with specific phytohormones. However, the regulatory mechanisms and key factors that control differentiation-dedifferentiation and cell totipotency have not been completely clarified in plants. Recently, several plant transcription factors that regulate meristem formation and dedifferentiation have been identified and include me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
0
21
0
1
Order By: Relevance
“…The first pattern (Figure S9A – Additional file 1 ) is composed by the transcriptional factor TCP5 (SP803280_c109776_g3) that monotonically increased its expression from B0 to T segments. Members of this family are involved with leaf morphogenesis and differentiation [ 68 70 ], arrest of cell division [ 71 ], leaf elongation [ 72 ] and auxin response [ 73 ]. To date, there is no information on the role of TCP5 in C 4 plants and its expression profile in our dataset suggests that this gene can be an important player during leaf development.…”
Section: Resultsmentioning
confidence: 99%
“…The first pattern (Figure S9A – Additional file 1 ) is composed by the transcriptional factor TCP5 (SP803280_c109776_g3) that monotonically increased its expression from B0 to T segments. Members of this family are involved with leaf morphogenesis and differentiation [ 68 70 ], arrest of cell division [ 71 ], leaf elongation [ 72 ] and auxin response [ 73 ]. To date, there is no information on the role of TCP5 in C 4 plants and its expression profile in our dataset suggests that this gene can be an important player during leaf development.…”
Section: Resultsmentioning
confidence: 99%
“…Phytoplasmas are bacterial pathogens that depend on phloem-feeding leafhoppers for transmission. The Aster Yellows phytoplasma strain Witches’ Broom (AY-WB) produces a Sec-secreted effector called SAP11, which destabilizes the TEOSINTE BRANCHED1, CYCLOIDEA, PROLIFERATING CELL FACTORS (TCP) class of transcription factors in Arabidopsis (Ikeda and Ohme-Takagi 2014 ). Among them, TCP4 activates the expression of JA biosynthetic gene LIPOXYGENASE 2 ( LOX2 ) (Schommer et al 2008 ).…”
Section: Plant Hormones As Key Regulators Of Immunitymentioning
confidence: 99%
“…Wounding was shown to promote regeneration-competent callus development from Arabidopsis roots in a WIND1 transcription factor-dependent way (Iwase et al 2011a, b;Ikeuchi et al 2016). Endogenous auxin level is not significantly changed in wounded Arabidopsis hypocotyls (Iwase et al 2017) and WIND1 has no effect on endogenous auxin level (Ikeda and Ohme-Takagi 2014;Iwase et al 2017) but was shown to activate cytokinin synthesis and responses (Iwase et al 2017).…”
Section: Discussionmentioning
confidence: 99%